2005
DOI: 10.1200/jco.2005.02.106
|View full text |Cite
|
Sign up to set email alerts
|

Objective Response to Chemotherapy As a Potential Surrogate End Point of Survival in Metastatic Breast Cancer Patients

Abstract: These results support the hypothesis that the achievement of an objective response to chemotherapy in metastatic breast cancer is associated with a true survival benefit. The potential role of objective response as a surrogate end point for survival in chemotherapy trials of metastatic breast cancer warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 29 publications
4
75
2
1
Order By: Relevance
“…For breast cancer, a moderately strong correlation between 2-year disease-free survival and 5-year overall survival was observed in the adjuvant setting (Ng et al, 2008). A meta-analysis of metastatic breast cancer studies found a positive relationship between objective response and overall survival on an individual patient basis, but the relationship was less clear when treatment regimens were compared (Bruzzi et al, 2005). The authors questioned whether the relationship was strong enough to support objective response rate as a valid surrogate of survival when comparing treatments.…”
mentioning
confidence: 99%
“…For breast cancer, a moderately strong correlation between 2-year disease-free survival and 5-year overall survival was observed in the adjuvant setting (Ng et al, 2008). A meta-analysis of metastatic breast cancer studies found a positive relationship between objective response and overall survival on an individual patient basis, but the relationship was less clear when treatment regimens were compared (Bruzzi et al, 2005). The authors questioned whether the relationship was strong enough to support objective response rate as a valid surrogate of survival when comparing treatments.…”
mentioning
confidence: 99%
“…Our results suggest that biomarker DT impact after therapy could be considered as a relevant surrogate marker of survival in progressive MTC treated by pRAIT. Validation of response to a given treatment as a surrogate of survival in a specific cancer condition requires ideally the availability of large datasets of patients randomly assigned to the tested treatment or to a control (34). However, in rare diseases such as MTC, randomized trials are difficult to implement because of the need to include a sufficient number of patients over an acceptable time period.…”
Section: Discussionmentioning
confidence: 99%
“…L'obtention d'une réponse objective semble conduire à un bénéfice en termes de survie (13,14), mais également de réduction des symptômes (15). Cependant, pour la majorité des patientes, il n'est pas démontré que la polychimiothérapie induise une survie supérieure à celle obtenue par monochimiothérapie (16), ce qui conduit plusieurs auteurs à s'interroger sur la meilleure stratégie (17, 18) et certains groupes à recommander une monothérapie (3-5) dans le but notamment de respecter la qualité de vie, hormis le cas des patientes porteuses d'une atteinte viscérale évolutive, nécessitant l'obtention d'une réponse thérapeutique rapide.…”
Section: Traitements En Phase Palliative Activeunclassified